2010
DOI: 10.1095/biolreprod.110.084947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effects of Prolactin in Gonadotroph Target Cells1

Abstract: Hyperprolactinemia is a major cause of infertility, brought about by inhibition of gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus and impairment of luteinizing hormone (LH) output from the pituitary gland. However, whereas the actions of prolactin (PRL) within the brain have been investigated extensively, its specific effects at the level of pituitary gonadotroph target cells remain unclear. Here, we provide evidence that the actions of PRL within the gonadotroph are more complex than or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Hyperprolactinaemia leads to a loss of fertility in female rodents (reviewed in [19]), suppressing pulsatile luteinizing hormone (LH) at both the level of the hypothalamus and pituitary [20,21]. This suggests an important role for PRL in timing of fertility to prevent a conflict between the metabolic requirements of pregnancy and lactation.…”
Section: Suppression Of Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperprolactinaemia leads to a loss of fertility in female rodents (reviewed in [19]), suppressing pulsatile luteinizing hormone (LH) at both the level of the hypothalamus and pituitary [20,21]. This suggests an important role for PRL in timing of fertility to prevent a conflict between the metabolic requirements of pregnancy and lactation.…”
Section: Suppression Of Fertilitymentioning
confidence: 99%
“…Whilst rodents have suppressed fertility during lactation, they have evolved a window of opportunity for mating with a postpartum ovulation immediately after birth, although there are mechanisms which delay implantation so that the subsequent litter is not born until the current pups are weaned [22]. Recent studies in rats have suggested that the pathway leading to this suppression of fertility is via kisspeptin neuron inhibition by the high PRL levels during lactation [23], together with direct effects upon LH release from pituitary gonadotrophs [20,24].…”
Section: Suppression Of Fertilitymentioning
confidence: 99%
“…In gonadotroph cell lines, e.g., αT3 (Henderson et al, 2008) and LβT2 cells (Hodson et al, 2010a), PRL treatment can elevate both basal and GnRH-induced LH release with a parallel drop in LHβ mRNA levels. However, similar studies in primary culture of pituitary cells, e.g, in sheep (Gregory et al, 2004) and horse (Hodson et al, 2010b), or whole pituitary culture, e.g. in rat (Cheung, 1983), were found to have opposite effects.…”
Section: Discussionmentioning
confidence: 74%
“…In ovine (Gregory et al, 2004) or equine pituitary cells (Hodson et al, 2010a), PRL treatment could reduce basal and block GnRHinduced LH secretion. However, similar treatment in mouse gonadotrophs was found to up-regulate LH release with no effects on LHβ mRNA levels (Hodson et al, 2010b). Of note, LH receptor (LHR) expression in lactotrophs has not been reported and it is still unclear if LH released locally can play a role in paracrine regulation of PRL at the pituitary level.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperprolactinemia is one of a major causes of infertility, brought about by inhibition of gonadotropin-releasing hormone (GnRH) or pulsatile GnRH secretion from the hypothalamus and impairment of LH output from the pituitary gland (27). PRL within gonadotroph cells are controlled by dopamine, the main hypothalamic inhibitory regulator of PRL release in vivo, this specific actions of PRL within the gonadotroph and the cell signaling interactions that ultimately underlie hyperprolactinemia-induced infertility (27); hyperprolactinemia can occur in physiological and pathological conditions (28) such as psychotic stress, severe mental illness or other causes, and the reproductive dysfunction affecting about one third of infertile women (29).…”
Section: Resultsmentioning
confidence: 99%